Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1037/a0017821
|View full text |Cite
|
Sign up to set email alerts
|

The social competence of Latino kindergartners and growth in mathematical understanding.

Abstract: We know that social competence contributes to young children's adaptation to, and cognitive learning within, classroom settings. Yet initial evidence is mixed on the social competencies that Latino children bring to kindergarten and the extent to which these skills advance cognitive growth. Building from ecocultural and developmental-risk theory, this paper shows children's social competence to be adaptive to the normative expectations and cognitive requirements of culturally bounded settings in both the home … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
137
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(156 citation statements)
references
References 54 publications
8
137
1
1
Order By: Relevance
“…A few studies have examined the long-term links between selfreliance in the classroom and children's achievement (e.g., DiPrete & Jennings, 2012;Galindo & Fuller, 2010;Li-Grining et al, 2010;NICHD Early Child Care Research Network, 2008;Stipek et al, 2010). Previous analyses of the NICHD Study of Early Child Care and Youth Development, for example, showed that higher levels of self-reliant behaviors in the classroom in Grades 1 and 3 predicted gains in math and reading achievement from preschool to Grade 3 (NICHD Early Child Care Research Network, 2008).…”
Section: Classroom Self-reliance and Academic Achievementmentioning
confidence: 99%
“…A few studies have examined the long-term links between selfreliance in the classroom and children's achievement (e.g., DiPrete & Jennings, 2012;Galindo & Fuller, 2010;Li-Grining et al, 2010;NICHD Early Child Care Research Network, 2008;Stipek et al, 2010). Previous analyses of the NICHD Study of Early Child Care and Youth Development, for example, showed that higher levels of self-reliant behaviors in the classroom in Grades 1 and 3 predicted gains in math and reading achievement from preschool to Grade 3 (NICHD Early Child Care Research Network, 2008).…”
Section: Classroom Self-reliance and Academic Achievementmentioning
confidence: 99%
“…A positive attitude towards the self and other people is an important aspect of social life, which makes for quality social relationship. So far, the results of the studies on the relationship between social competence and academic performance have proved positive except Galindo and Fuller (2010) study, which examined the relationship between social competence and Mathematics understanding. The findings of Galindo and Fuller (2010) study suggested no association between the two variables and the study, therefore, concluded that the competencies that Latino children bring to kindergarten and the extent to which these skills advance cognitive growth were mixed.…”
Section: Importance Of Social Competence To Academic Achievementmentioning
confidence: 99%
“…It is a key skill as children need to manage social situations by learning from past experiences and applying the experiences to new contexts, build positive relationships with peers, and feel good about themselves (Blair, Denham, Kochanoff, & Whipple, 2004;Semrud-Clikeman, 2007;Wentzel, 1999). Higher social competence levels in children are predictive of school readiness and early academic success as children can quickly adjust to classroom routines (Denham, 2006;Galindo & Fuller, 2010). Conversely, lower social competence levels may compromise children's mental and physical health, peer relationship and school achievement (Rose- Krasnor, 1997;Semrud-Clikeman, 2007).…”
Section: * Shirley Wyvermentioning
confidence: 99%